Experimental Comparison of Phytoremediation and Filtration Methods in the Remediation of Water Contaminated with Arsenic - Temitope Ayodeji Laniyan; Akinlolu Festus Abimbola; M K.C Sridhar (International Journal of Phytomedicine, 2015)
An experimental work was done on waters contaminated with arsenic using filtration and phytoremediation methods to determine the most appropriate remediation method. Filtration method; Measurements of arsenic solution (0.00g (de-ionized water), 0.010g, 0.020g, 0.050g, and 0.0100g) was made by a 10litre pipette into an hundred milliliter bottle (100ml) containing warm de-ionized water and each was made to pass through four different geo-materials (marble, activated charcoal, filtration carbon and clay) placed on layers of sand in glass filtration tanks ; while Phytoremediation method was done by cultivation of various ages of water hyacinth (Eichhornia crasspipes Mart. Solms) in arsenic acid solution of equal concentration (100.0 mg/L); an experiment based on duration and maturity which was to ascertain the exact hour, (0hour, 2hours, 12hours, 24hours, 48hours, 120hours) water hyacinth will absorb a metal, and at what matured level (sprouting, flowering, matured) the plant can absorb best. Plants were harvested, dried, pulverized and analysed for metal content using inductively coupled-ion chromatography and filtrates analysed using inductively coupled plasma-optical emission spectrometry. Arsenic concentration in filtrates showed no arsenic loss, indicating poor absorption capacity of the geo-materials. Highest arsenic bio-accumulation was found at 100 mg/l in matured water hyacinth. Remediation of arsenic using water hyacinth proved to be a better method for arsenic removal compared to filtration.